Medium-chain triglycerides improved cognition and lipid metabolomics in mild to moderate Alzheimer's disease patients with APOE4−/−: A double-blind, randomized, placebo-controlled crossover trial. Issue 7 (July 2020) - Xu, Qing; Zhang, Yong; Zhang, Xinsheng; Liu, Lu; Zhou, Bo; Mo, Rui; Li, Yan; Li, Huizi; Li, Feng; Tao, Yang; Liu, Yinghua; Xue, Changyong
Summary: Background: Previous clinical and animal studies suggested that medium-chain triglycerides (MCT) might be an alternative energy substrate for the brain and might benefit patients with Alzheimer's disease (AD), but the clinical evidence is not substantial or totally convincing. Objective: To investigate the effects of MCT on cognitive ability in patients with mild to moderate AD and explore the changes in peripheral blood metabolomics. Methods: A double-blind, randomized, placebo-controlled crossover study was undertaken in 53 mild to moderate AD patients. Participants were randomized between two sequences (placebo followed by MCT or MCT followed by placebo) and took MCT jelly or placebo jelly (canola oil) by mouth three times daily (total daily fat dose: 17.3 g MCT, or 19.7 g canola oil) for 30 days per phase. The primary outcome was cognition as measured by the Alzheimer's Disease Assessment Scale–Cognitive Subscale, Chinese version (ADAS-Cog-C). The secondary outcome was self-care as measured by the activities of daily living scale (ADL) and changes in plasma metabolites. Results: This study showed a significant ( p  < 0.01) reduction in ADAS-Cog-C scores between the MCT (2.62 points below baseline) and placebo interventions (2.57 points above baseline). Data from 46 (86.8%) APOE4 −/− subjects who completed the entire study were analyzed. Changes in ADL scores were not significantly different between the MCT and placebo interventions ( p  > 0.05). The concentrations of TC, HDL-C, β-hydroxybutyrate and acetoacetate were significantly higher in the MCT group than in the placebo group ( p  < 0.05). Lysophosphatidylcholine 16:0 (LysoPC (16:0)), LysoPC (P-18:0), LysoPC (P-18:1(9Z)), LysoPC (20:2(11Z, 14Z)), and LysoPC (22:5(4Z, 7Z, 10Z, 13Z, 16Z)) were significantly increased after MCT intervention, and the concentrations of LysoPC (18:0), palmitic acid, linoleic acid, oleic acid, and 7, 12-dimethylbenz[a]anthracene were significantly decreased ( p  < 0.05), whereas no significant changes appeared after the placebo intervention. Androstenedione concentration increased after placebo intervention. Furthermore, a significant negative correlation was observed between changes in LysoPC (P-18:1(9Z)) and ADAS-Cog-C scores after MCT intervention (r = −0.1472, p  < 0.05). Conclusions: MCT had positive effects on cognitive ability in mild to moderate AD patients with APOE4 −/− . These effects of MCT might be related to the metabolism of LysoPC, oleic acid, linoleic acid and palmitic acid, in addition to the ketogenic effect. Study ID number: ChiCTR-IOR-16009737. Registry website: WHO ICTRP Search Portal – http://apps.who.int/trialsearch/Default.aspx .